THE COMMUNICATIVE PERSPECTIVE IN TRANSLATION STUDIES: A MOROCCAN UNIVERSITY CASE STUDY - Abdellah El Boubekri; Marilyn Lewis (ELTR Journal, 2021)
Translation of written texts has been a part of international communication for centuries, but courses in how to do it are more recent. This study reports a case study from the context of a Moroccan university where translation courses are taught in two parts. In one semester the students learn about translation from English to Arabic and the next from Arabic to English. We report the teachers’ perspectives on the translation course from Arabic into English, along with the results of the students’ translations based on 400 examination answers. The analysis and discussion of the results will reveal the shortcomings for the current teaching practice of translation; they will also suggest new ways of customizing the course for more effective acquisition of English language as a medium for boosting intercultural communication, the most probable prerequisite for today’s access in the job market.